The Influence Of The Make A Match Method For Mastering Mufradat At Al-Qur'an Middle School Salafiyyah Syafi'iyyah Sukorejo Bangorejo Banyuwangi - Alya Afifah Maliyanah; Munirul Abidin; Muhammad Ichsan (Lahjatuna: Jurnal Pendidikan Bahasa Arab, 2024)
Vocabulary teaching is an important aspect in language acquisition because mufradat is the key to the teaching and learning process. The researcher used the make a match method for mastery of mufradat at SMP Al-Qur'an Salafiyyah Syafi'iyyah Sukorejo Bangorejo Banyuwangi. The purpose of this study was to determine the effect and results of student learning using the make a match method for mufradat mastery at SMP Al-Qur'an Salafiyyah Syafi'iyyah Sukorejo Bangorejo Banyuwangi. This research method uses quantitative methods using Experimental with the research design using the One-Group Pretest-Posttest Design. The sample of the research was 15 grade 9 students of SMP Al-Qur'an. Data collection techniques using observation, interviews, documents, pretest and posttest. The results of the normality test, there is a normal distribution population that is used in the experimental post-test and control post-test. the results of the homogeneity test produce a sig value > 0.05 = homogeneous, meaning that the data is taken from the same population. And in the Paired T-Test there is a significant effect on the pretest and posttest classes, namely from an average of 77.00 it has increased to 82.33.